As não-coincidências interlocutivas do dizer de sujeitos hispanos-falantes em discursividades brasileiras : seus reflexos em formulações imaginárias - Morais, Valdete de Lima Ank (Universidade Federal de São Carlos, 2008)
Based upon French Discourse Analysis, our purpose in this study is bring and analyze discursive sentences produced by Spanish native speakers, symptoms of their enunciative projections, imaginary and discursive memories, in relation to their concepts, impressions, allusions concerning Portuguese language and Spanish language, in situations of immersion and interlocution in Brazilian contexts. We start from Serrani-Infante s (1998) formulations, that the subject, when speaking another language, becomes part of the identification process in the target language discursive formations that build up the happening of enunciative positions. In order to realize this study it is necessary to understand the insertion of the Spanish native speaker in Brazilian Portuguese language in the immersion process as a subjective process (SERRANI, 1997b), which requires the subjectivity from the Spanish native speaker and will submit him to inscribe himself in different enunciative positions, missteps, displacements and transference motions (CELADA, 2004). Thus, we understand that part of these enunciative positions is associated with the Spanish native speaker s mother tongue, with their own language positions, and that many of them are brought up in the encounter with the foreign language, leading the subject to conflict situations generated by the distinct understanding of reality linked to those two languages. These conflict situations, concerning the processes of production and attribution of meanings by native speakers of Spanish as they enunciate in Brazilian Portuguese language, constitute the focus of this study.
Keywords: Lingüística; Ensino - aprendizagem; Língua materna; Memória; Identificação; Sujeito hispano-falante; Representações; Spanish native speaker; Mother tongue; Representation; Memory; Identification; LINGUISTICA, LETRAS E ARTES::LINGUISTICA